2017
DOI: 10.4236/ojoph.2017.73020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Funduscopic Exam of Pediatric Patients Using the D-EYE Method and Conventional Indirect Ophthalmoscopic Methods

Abstract: Purpose: The D-EYE device, a new fundoscopic smartphone lens, has demonstrated its utility in a clinical setting to detect and document ocular pathology, but has not been tested in the pediatric population. A prospective study was performed to explore the application of D-EYE in pediatric fundus examinations. Methods: Patients ages 3 -18 years old underwent dilated fundus examinations by masked examiners using the video function of the D-EYE, while indirect ophthalmoscopy was performed by apediatric ophthalmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…We used the D-EYE digital ophthalmoscope (D-EYE Srl, Padova, Italy), a magnetic lens that attaches to the smartphone via magnets to transform the smartphone into a portable fundus camera (Figure 1). The D-EYE is Food and Drug Administration approved as a fundus camera and also has a secure HIPAA compliant cloud software to store images 21. Clinical studies using the D-EYE have found it to be superior in detecting fundus findings of acute hypertension compared with direct ophthalmology in the ER setting, showed significant agreement with slit-lamp biomicroscopy in measuring vertical cup to disc ratios, and was comparable with indirect ophthalmoscopy in detecting fundus findings in pediatric patients 17,18,21,22…”
Section: Introductionmentioning
confidence: 99%
“…We used the D-EYE digital ophthalmoscope (D-EYE Srl, Padova, Italy), a magnetic lens that attaches to the smartphone via magnets to transform the smartphone into a portable fundus camera (Figure 1). The D-EYE is Food and Drug Administration approved as a fundus camera and also has a secure HIPAA compliant cloud software to store images 21. Clinical studies using the D-EYE have found it to be superior in detecting fundus findings of acute hypertension compared with direct ophthalmology in the ER setting, showed significant agreement with slit-lamp biomicroscopy in measuring vertical cup to disc ratios, and was comparable with indirect ophthalmoscopy in detecting fundus findings in pediatric patients 17,18,21,22…”
Section: Introductionmentioning
confidence: 99%
“…pathology grading systems) and for use within telehealth [ 20]. While there is evidence supporting use of smartphones in various areas of ophthalmology [2023]; evidence of their usefulness as an educational tool is still emerging. Early reports suggest medical students view smartphone ophthalmoscopes favourably and are more likely to make correct and faster diagnoses than when using direct ophthalmoscopes [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…The PanOptic iExaminer SF was shown to be effective in obtaining clinically adequate fundus images amongst 91% of 2–18‐year‐old children in the ED, but achieved only 16% amongst children 0–2 years old [42]. Likewise, the D‐EYE demonstrated good diagnostic agreement with the gold standard amongst a paediatric population [17].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the specificity of SF compared with NMFP with a 10% width to the 95% CI at 5% α , a cohort of 16 participants would be required based on an estimated specificity of 0.92 from previous studies [17].…”
Section: Methodsmentioning
confidence: 99%